Relationship between newborn care knowledge, attitudes toward child-rearing, parental role confidence, and the expected number of children among university students in a region of South Korea - Lee, Sung Hee; Lee, Seung A (Edelweiss Applied Science and Technology, 2025)
In 2023, the total fertility rate in South Korea was 0.72, the lowest among all Organization for Economic Cooperation and Development countries. The country’s low birth rate is influenced by sociocultural factors, including negative perceptions of children and child-rearing, particularly among unmarried men and women. Shaped by these factors, the expected number of children among university students serves as a predictor for future fertility rates. This descriptive survey explored factors influencing the expected number of children among university students in a specific region of South Korea. It examined the relationship between students’ knowledge of newborn care, attitudes toward child-rearing, parental role confidence, and their expected number of children. Data were collected in August 2024 from 100 students enrolled in the Healthy Parenting Recipes course at K University in Daegu. A total of 78 valid responses were analyzed using descriptive statistics and ordinal logistic regression with SPSS/PC Version 29.0. The results showed that participants who prioritized maternal career (exp(B) = .381, CI: .151–.610, p = .001) and those with greater parental role confidence (exp(B) = .132, CI: .010–.254, p = .034) are more likely to desire a higher number of children. These results suggest that fostering an environment where women can balance work and childcare may increase fertility rates. Additionally, enhancing parental role confidence through parenting education may increase the expected number of children among unmarried men and women. Overall, the findings offer valuable insights for policies to address South Korea’s low birth rate.